Determinants of family support and its impact on self-care behavior among patients with type 2 diabetes in community settings: a cross-sectional analytical study - M. Khalid Fredy Saputra; Hijrah Hijrah; Wawan Kurniawan; Anita Lontaan; Rasi Rahagia (LPPM Politeknik Sandi Karsa, South Sulawesi, Indonesia, 2026)
Introduction: Suboptimal adherence to self-care remains a persistent challenge in the management of type 2 diabetes mellitus (T2DM), particularly in community settings where daily disease control largely depends on patients’ behavioral practices. While family support is often considered influential, its relative contribution compared with other factors remains unclear. This study aimed to examine the determinants of family support and assess its impact on self-care behavior among patients with T2DM. Research Methodology: A community-based, cross-sectional, analytical study was conducted involving 125 patients with T2DM, selected through purposive sampling. Data were collected using validated instruments assessing family support and self-care behavior. Statistical analysis included descriptive statistics, bivariate tests, and multivariable logistic regression to identify independent predictors, with a significance level set at p < 0.05. Results: High family support was significantly associated with better self-care behavior (adjusted OR = 3.35; 95% CI: 1.65–6.80; p = 0.001). Higher educational level was also independently associated with improved self-care (AOR = 2.03; 95% CI: 1.01–4.09; p = 0.047). Other variables, including age, diabetes duration, and comorbidities, were not statistically significant in the adjusted model. Conclusion: Family support is the strongest determinant of self-care behavior among patients with T2DM in community settings. Integrating family-based approaches into diabetes management programs may enhance adherence to self-care and improve long-term outcomes. Health policies should prioritize family-inclusive interventions as part of comprehensive diabetes care.